Overthinking pada Generasi Z dalam Kerangka Psikologi Al-Qur’an: Distingsi antara Tafakkur, Waswas, dan Qalq - Mutiara Fahliza; Muhammad Hidayat; Siti Ismahani (Yayasan Albahriah Jamiah Indonesia, 2026)
The phenomenon of overthinking among Generation Z is intensifying alongside mounting academic, social, and digital pressures; however, modern psychological approaches often frame it merely as a cognitive symptom, overlooking deeper spiritual dimensions. This paper aims to establish conceptual distinctions between tafakkur, waswas, and qalq within the framework of Qur’anic psychology to provide a more comprehensive understanding of the mental dynamics of the contemporary generation. A qualitative, library-based approach was employed, utilizing the thematic exegesis mawḍūʻī method combined with semantic and conceptual analyses of key Qur’anic terms. The results reveal clear differentiations: tafakkur functions as constructive cognitive reflection directed toward meaning and wisdom; waswas emerges as a repetitive, irrational cognitive distortion that undermines self-integration; and qalq represents an affective manifestation—an inner restlessness rooted in an imbalance between cognition and spirituality. Together, these three form an interconnected spectrum of mental experiences, yet each possesses distinct epistemic and functional characteristics. These findings underscore the capacity of the Qur’anic psychological framework to provide a more holistic and integrative conceptual classification capable of bridging cognitive and affective dimensions in the understanding of overthinking, while simultaneously paving the way for the development of psychological intervention models grounded in Qur’anic values ​​systematically and contextually.